The comparison respond of braking torque control between PID and SMC controller for electric powered wheelchair descending on slope condition - Mohamad Heerwan, Peeie; S. M., Asyraf; Muhammad Izhar, Ishak (IOP Publishing Ltd, 2018)
During descending on a slope, the speed of Electric Powered Wheelchair (EPW) tends to changed rapidly. Normally, most EPW is provided with mechanical braking system which transfers human pulling force of the lever creating friction at the tire. However, the task is difficult for the users are elderly or paralyses. However, even for normal user with good strength, in fear condition they tend to give sudden braking which leads to tire locking up and skidding, eventually EPW unstable. These problems will cause accident and injuries to the users if speed does not properly control. In this paper, the automated braking torque control method was proposed in EPW as alternative to solve this problem and increase the mobility and stability especially during descending on slope in other to help the user of the EPW as their daily transportation. In this research, Proportional-Integral-Derivative and Sliding Mode Control controller are compared to determine the best response for torque braking control. The rapid change of speed can be controlled by the braking torque using proposed controllers based on the desired constant speed set by the control designer. Moreover, the sudden braking that caused tire to lock up and skid can be avoided. Furthermore, result from SMC shows this controller have good time respond to maintain the speed based on desired value when descending at slope condition by controlling the braking torque compared to the PID controller.